Determination of Direct and Indirect Costs Incurred by Tuberculosis Patients During Diagnosis and Treatment in Urban Areas of South Gujarat: A Mixed Method Approach - Rutu Buch; Rahul Damor; J. K. Kosambiya (Wolters Kluwer Medknow Publications, 2024)
Though many initiatives and monetary benefits are incorporated under RNTCP/NTEP, many patients might incur some out-of-pocket expenditure (OOP) related to diagnosis, treatment, and hospitalization. Such costs lead to further poverty and default. This study estimated OOP costs. A cross-sectional mixed method study was conducted in 2020. Data were collected from two selected UHCs (both public and private sectors) from all eight administrative zones. A total of 278 newly registered drug-sensitive tuberculosis patients at different stages of treatment were enrolled, and 18 IDIs were done after obtaining the consent. Among 278, 231 (83%) were seeking the treatment from the public sector and 47 (17%) from the private sector. The average direct, indirect, and total costs were Rs. 8812, Rs. 4825, and Rs. 13,637, respectively. Extra food and supplements are the major field of expenditure for those enrolled in the public sector. Higher costs were incurred by the private sector patients. Longer distances, a long waiting time, belief systems, and unavailability of facilities or drugs were the common reasons for not visiting the public sector. IDI results also supported the cost heads. The majority of the expenses occurred at the private settings before diagnosis. IDIs suggested to changes in the programmatic approach toward migrants, industrial workers, and women.